Real-world effectiveness and safety of bulevirtide monotherapy for up to 96 weeks in patients with HDV-related cirrhosis - Degasperi, Elisabetta; Anolli, Maria Paola; Jachs, Mathias; Reiberger, Thomas; De Ledinghen, Victor; Metivier, Sophie; D’Offizi, Gianpiero; di Maria, Francesco; Schramm, Christoph; Schmidt, Hartmut; Zöllner, Caroline; Tacke, Frank; et al. (Journal of hepatology, 2025)
Background & Aims - Bulevirtide (BLV) 2 mg/day is EMA approved for the treatment of compensated chronic HDV infection; however, real-world data in large cohorts of patients with cirrhosis are lacking. - Methods - Consecutive HDV-infected patients with cirrhosis starting BLV 2 mg/day from September 2019 were included in a European retrospective multicenter real-world study (SAVE-D). Patient characteristics before and during BLV treatment were collected. Virological, biochemical, combined responses, adverse events and liver-related events (hepatocellular carcinoma [HCC], decompensation, liver transplant) were assessed. - Results - A total of 244 patients with HDV-related cirrhosis receiving BLV monotherapy for a median of 92 (IQR 71-96) weeks were included: at BLV start, median (IQR) age was 49 (40-58) years and 61% were men; median ALT, LSM and platelet count were 80 (55-130) U/L, 18.3 (13.0-26.3) kPa, and 94 (67-145) x103/mm3, respectively; 54% had esophageal varices, 95% Child-Pugh A cirrhosis, and 10% HIV coinfection; 92% were on nucleos(t)ide analogues; median HDV RNA and HBsAg were 5.4 (4.1-6.5) log10 IU/ml and 3.8 (3.4-4.1) log10 IU/ml, respectively. At weeks 48 and 96, virological, biochemical and combined responses were observed in 65% and 79%, 61% and 64%, 44% and 54% of patients, respectively. AST, GGT, albumin, IgG and LSM values significantly improved throughout treatment. Serum bile acid levels increased in most patients, but only 10% reported mild and transient pruritus, which was independent of bile acid levels. The week 96 cumulative risks of de novo HCC and decompensation were 3.0% (95% CI 2-6%) and 2.8% (95% CI 1-5%), respectively. Thirteen (5%) patients underwent liver transplantation (n = 11 for HCC, n = 2 for decompensation). - Conclusion - BLV 2 mg/day monotherapy for up to 96 weeks was safe and effective in patients with HDV-related cirrhosis. Virological and clinical responses increased over time, while the incidence of liver-related complications was low. - Impact and implications - Bulevirtide 2 mg/day is EMA approved for the treatment of compensated chronic hepatitis delta; however, real-world data in large cohorts of patients with cirrhosis are lacking. Bulevirtide 2 mg/day monotherapy for up to 96 weeks was safe and effective (week 96: 79% virological, 64% biochemical and 54% combined response) in a large real-world cohort of patients with HDV-related cirrhosis, including patients with clinically significant portal hypertension. Liver function tests and liver stiffness improved, suggesting a potential clinical benefit in patients with advanced liver disease, while the incidence of de novo liver-related events (hepatocellular carcinoma and decompensation) was low during the 96-week study period.